The potency of natural and synthetic composites for ballistic resistance: A review - Yaakob, Mohd Yuhazri; Saion, Mohamad Pazlin; Husin, Mohd Amirhafizan (Applied Research and Smart Technology (ARSTech), 2020)
Mechanical characteristics of the laminated composite crafted from fabric type reinforcement perhaps inspired via the weaving method and reinforcement agent's usage due to each layer's constructional parameter. As a result, research on the arrangement configuration between bio composite and synthetic fibre for the material shape was proposed to enhance the composite structure's biodiversity and physical characteristics. Substitute for natural fibre in synthetic fibre composite works has shown the excessive capacity to be explored scientifically. The evaluation focused on the concept and essential of bio composite and the synthetic composite fabric positioned over the years from the previous studies of the preliminary researches. The sorts and features of matrix and fibre filler reinforcement materials in composites were also discussed. This assessment's main findings indicated that the composite centre relied on the weave styles and inter-ply and interplay lamination roles. Therefore, the state-of-the-art intraply for synthetic fibre and bio composite fibre in a composite shape was anticipated performing higher in mechanical energy, particularly within the application of ballistic resistance, besides decreased dependency on artificial fibre. It would ultimately suggest the excellent weave sample designs in the proper combination shape of natural and synthetic fibres embedded with polymers. The statistical results were compared with the experimental parameters available inside the literature review. The review explains approximately the studies and evolution within the enhancement of characteristic fibres reinforced polymer composites in ballistic resistance use. This paper goes over the body armour's profitable and present advancement materials, structure and development procedures, and related works on upgrading ballistic energy captivation and upgrading the mechanical tenacity for high impact resistance applications.